Faktor ibu bapa dalam kecemerlangan akademik pelajar pekak: Kajian kes retrospektif - Othman, Shahrul Arba'iah; Azman, Norzaini; Mohd Ali, Manisah (UUM College of Arts and Sciences, 2008)
The purpose of this retrospective case study is to understand how family factors have contributed to the academic excellence of deaf students. Academic excellence is defined as the deaf student’s success in the public examinations which enabled them to continue their studies at diploma or degree level. Eight deaf students who excelled in their studies, and all the mothers and four fathers of these students participated in this study. Data were gathered by triangulating several methods and sources. Methods used were in-depth interviews, written answers, and document analysis while the informants were parents, deaf students, and documents/memorabilia. In-depth interviews were carried out with the parents and supporting information was gathered in written form from the deaf students and document analysis. Data were processed using verbatim transcript analysis and were analyzed thematically. Findings showed that the deaf students’ academic excellence was due to two factors, that is family and the deaf students themselves. Parental factors that are considered important are parent’s attitudes, parent’s involvement, parent’s expectations, family environment, and family resources. This study has implications for the implementation of better early intervention services, equal opportunities in education for deaf students, and collaborations between agencies involved in providing services.